A resiliência: um processo potencial de proteção e adaptação do bem-estar psicológico na velhice - Nadaf, Vania Cristhina (2013)
The increasing extent of human life and the number of elderly in the population, aging has become a privileged theme and one of the great challenges of contemporary society. Aging has been considered as a period of great adversity and increased stress (higher familiarity with the risk) may also be considered as a new stage of life that might be positively experienced. Studies have demonstrated that for such positive experience, the resilience is critical, since it is linked to intrapsychic processes of protection and risk and social interaction, which has relevance in the process of adapting and overcoming the diversity of this stage of life. Tied to the resilience it is the measure of life satisfaction, characterized as performing a cognitive judgment of some specific domains of life and reflects how persons perceives their lives concerning the present, the past and their expectations to the future. This construct is also comprehended as essential cognitive component that complements happiness. The need of studying these constructs, this research was emerged aimed at examining the associations between the capacity of resilience and perceived stress with the cognitive component Subjective well-being (SWB) - the satisfaction with life - in a sample of elderly in Cuiabá, in the state of Mato Grosso. The theoretical model of human development, with a deep influence of Psychosocial Theory of Erikson (1972) and Grotberg s model that defines resilience as a concept associated to human and growth development. Method: This research is characterized as a cross-sectional study of quantitative approach. It was divided into two studies; the first consisted in adapting the Resilience Scale for Adults - RSA (Friborg, Hjemdal, Rosenvinge & Martinussen, 2003) that was submitted to a number of 200 elder participants. In the second study, the sample consisted of 379 elder participants who answered a sociodemographic questionnaire, the RSA scale (Hjemdal, et al. 2006), the Perceived Stress Scale (PSS) by Cohen, Karmack & Mermelsteinm (1983), Satisfaction with life Scale (SWLS) (Diener, 1985), and scale Hospital Anxiety and Depression (HADS) Zigmond & Snaith of (1983). The data were processed by the software Statistical Package for Social Science (SPSS) version 21 for the statistical analysis. The results obtained in the study I showed the predominance of women (n = 146) with an average of 67.23 years (SD = 5.9). The findings concerning the Factorial Analysis done in the study I indicated two dimensions - Family Cohesion (alpha = 0.95) and Optimism (alpha = 0.88) and two items were eliminated, thus, the RSA totalized (alpha = 0.91) adapted with 31 items for the elderly people. The results of the study II indicated that the sample has an average score of resilience and the majority of the elderly people answered to be satisfied with their lives. The results also revealed that elderly participants who had higher averages on assessments of RSA and SWLS had lower scores on scales PSS and HADS- Anxiety and depression. The hypothesis of the study I was not confirmed, suggesting that resilience may be measured differently for the elderly people, for the reason that the resilience at this life stage may be reflected in their positive adaptation processes in a psychological mature stage. In study II, the results confirmed the hypothesis of this research, the women had higher scores in RSA and its dimensions, and only in the optimism dimension this difference was significant. Based on the obtained results, it was concluded the need to advance in further research XIX to better understand the effects and consequences of the capacity of resilience in old age, as the findings of this study revealed the notion of a protective and promoter factor of welfare in this life phase. Old age brings losses concerning health, labor capacity, purchasing power and interpersonal relationships. Consequently, the constant presence of the item life satisfaction after 60 years reveals that resilience as a process of adaptation and overcoming the adversities imposed by life, became fundamental to not only to maintain the sense of certainty of having quality life, but also in the way these losses are absorbed and resignified in the lives of the elderly people.